Tinnitus Mechanisms, Comorbidities and Emerging Therapeutic Strategies - Fitria Waffi Nur Aini; Agus Surono; Ashadi Prasetyo (UMSU, 2026)
Tinnitus is the perception of sound without an external source and affects about one tenth of the population, with a small proportion experiencing severe disability. It arises from cochlear injury, central auditory hyperexcitability, maladaptive neuroplasticity, and involvement of limbic, prefrontal, and somatosensory systems, with additional contributions from inflammation, oxidative stress, and metabolic factors. This narrative review summarizes current concepts of tinnitus mechanisms, frequent psychological, auditory, somatosensory, and systemic comorbidities, and available treatments. The strongest evidence supports psychological and sound based interventions such as cognitive behavioral therapy, counseling, hearing rehabilitation, and tinnitus retraining therapy, which reduce distress and improve daily functioning even when loudness changes little. Pharmacological therapy mainly targets comorbid depression, anxiety, sleep disturbance, inflammation, and oxidative stress. Adequate intake of zinc and iron may help prevent tinnitus. Despite several promising options, clinical evidence remains heterogeneous and no single therapy is universally effective, so individualized multidisciplinary care informed by underlying mechanisms and further supported by advances in basic research, biomarker development, and rigorous clinical trials is required.